Frederic Vinton papers - Vinton, Frederic, 1817-1890.
Chiefly letters addressed to Vinton relating to library science and personal matters. Correspondents include William E. Alden, S. Austin Allibone, Charles A. Cutter, Joseph Sabin, Anne Shaw, Alfred Vinton, Sarah A. Vinton, and William Adolphus Wheeler.
Assistant Librarian of Congress.
Collection material in English.
Collection related to the Library of Congress Archives.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Alden, William E. -- Correspondence; Allibone, S. Austin -- 1816-1889 -- Correspondence; Cutter, Charles A. -- 1837-1903 -- Correspondence; Sabin, Joseph, -- 1821-1881 -- Correspondence; Shaw, Anne -- Correspondence; Vinton, Alfred -- Correspondence; Vinton, Sarah A. -- Correspondence; Wheeler, William Adolphus, -- 1833-1874 -- Correspondence; Library of Congress -- Officials and employees; Library science; Librarians